Violet the Pilot - Breen, Steve (New York : Dial Books for Young Readers, 2008)
Young Violet's only friend is her dog, Orville, until one of her homemade flying machines takes her to the rescue of a Boy Scout troop in trouble.
Accelerated Reader AR